Copper deficiency‐related bone marrow changes secondary to long‐term total parenteral nutrition. Issue 2 (29th December 2016) - Oo, Thein Hlaing; Hu, Shimin
Key Clinical Message: Total parenteral nutrition can be complicated by the marrow sea‐blue histiocytes as well as copper deficiency‐related bone marrow changes. Cytoplasmic vacuoles in the erythroid and myeloid precursors raise the possibility of copper deficiency anemia. If the diagnosis is delayed, the clinical course can be complicated by neurologic deficits. Abstract : Total parenteral nutrition can be complicated by the marrow sea‐blue histiocytes as well as copper deficiency‐related bone marrow changes. Cytoplasmic vacuoles in the erythroid and myeloid precursors raise the possibility of copper deficiency anemia. If the diagnosis is delayed, the clinical course can be complicated by neurologic deficits.